On the meaning of ConWIP cards: an assessment by simulation - Thürer, M. (2020)
This is an Accepted Manuscript of an article published by Taylor & Francis in Journal of Industrial and Production Engineering on 13/02/2019, available online: https://www.tandfonline.com/doi/full/10.1080/21681015.2019.1576784